Prediction Of Dynamics Of Insider Threat Of Sabotage Using The System Dynamics Modeling - Vladimir Sergeevich Makeev; Anton Sergeevich Zaytsev (Безопасность информационных технологий, 2015)
This article present a research of the threat of it-sabotage with the use of information resources of organization.Based on statistical information and relevant research, here was designed a system-dynamic model and represented results of test simulations.